PENGARUH MOTIVASI DAN PERSEPSI RISIKO TERHADAP MINAT BERKUNJUNG KEMBALI KE EKOWISATA TAMAN HUTAN RAYA NGURAH RAI PADA MASA PANDEMI COVID-19 - Leonita, Winda; Suardana, I Wayan; Kristianto, Yohanes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022)DO - 10.24843/IPTA.2022.v10.i02.p19, 2023)
Travel is inseparable from the motivation that drives an individual/group to travel. In addition to motivation, there are also other factors that influence tourist decisions, namely the image of the destination that later formed perceptions. Among the various kinds of influential tourist perceptions, there is perception of risk which is one of the key determinants in tourists’ decision-making process. This study was conducted with the aim to know how to influence of motivation and perceived-risk on tourist interest in making return visits to the Ngurah Rai Grand Forest Park (TAHURA) tourist attraction during the Covid-19 pandemic. In this study, a purposive sampling technique was used by distributing questionnaires via google form to 100 tourists who had visited TAHURA Ngurah Rai at least once. The data obtained from the questionnaire was then processed quantitatively with likert sale, then validity and reliability test were carried out with the outer loadings limit of 0,5. The data analysis technique used in this research is SEM-PLS analysis with the help of SmartPLS version 3.3.5 program. Based on the results of the data analysis, it is known that there is a positive and significant influence between motivation and revisiting intention, while there is a positive but insignificant influence between perceived risk and revisiting intention.